Potential Asiatic Acid in Centella asiatica (L.) Urban Towards NMDA Receptors of Alzheimer Dementia Patients In Silico - Widodo, Ayudisty Ristika Kusumawardhani; Rahmayanti, Rahmayanti; Shahab, Fatinah (Ahmad Dahlan Medical Journal, 2023)
Alzheimer's dementia can occur due to an increase in the neurotransmitter glutamate which can affect synaptic plasticity. Centella asiatica (L.) Urban is considered as one of the herbal plants used in the treatment of various diseases, such as medicine for leprosy, thrush, fever, hypertension, diabetes, and anemia and has a high antioxidant effect, one of the active ingredients is asiatic acid. This research to determine asiatic acid potential for NMDA receptors in Alzheimer's dementia. This research is an experimental research using a computer. The applications used were PyMOL for ligand preparation, PyRx for docking, and LigPlot for amino acid residue analysis. The interaction of receptor ligand binding is seen from the binding affinity score, the smaller the binding affinity score, the greater the potential between the ligand-receptors to interact. The pharmacokinetics of a compound are based on Lipinski's rule. In this study, the binding affinity score of - 8.3 was obtained and the Lipinski test showed the result of 'yes'.